Development of Manufacturing System in the Industrial Revolution 4.0 from Concept to Industrial World - Iwan Harianton; Heri Setiawan; Agus Surjana Saefudin (Jurnal Teknologi dan Rekayasa Manufaktur, 2020)
Industrial development in the new emerging countries were becoming attractive to OEM manufacturers since a decade ago by proofing stronger reliability of the industrial system enhanced by most countries separately. Especially, after the publicity of the German Government’s campaign on its Industrial Revolution 4.0 by smart factory, where more and more digital technology being created and launched to the market. This unique period is called the disruptive innovation where previous generation before millennials are still in the productive ages while all the digital techies invades almost all professional tools regarding of the common practices used by them. However, while such rapid changes are continuously occurring, most productive aspects of communities’ response positively to their youngsters by letting them lead most of the productive arenas with their excellent seamless leadership handover. The manufacturing world is among the leading sectors to response to the disruptive innovation by mapping all the system’s requirement to be implemented by millennial for responding the global world by structuring the concept of community-based companies into world class manufacturers. The process of rapid transformation in the manufacturing world was done in the suppliers of most OEM companies by structuring levels of their manufacturing system and enhancing facilities by equipping digital technology in their production machineries and also satisfying the key performance indicators of being reliable vendors. The enhancement track records were researched and made available to public by the local government agents so that more medium scale companies could cope with their projects of supplying goods to meet OEM companies’ requirement. The methodology of manufacturing system development is discussed in this paper including the benefits for some industries leading to catch up with their own development programs leading to global competitive players.